Circadian regulation of abiotic stress tolerance in plants - Grundy, Jack; Stoker, Claire; Carré, Isabelle A. (Frontiers in Plant Science, 2015)
Extremes of temperatures, drought and salinity cause widespread crop losses throughout the world and impose severe limitations on the amount of land that can be used for agricultural purposes. Hence, there is an urgent need to develop crops that perform better under such abiotic stress conditions. Here, we discuss intriguing, recent evidence that circadian clock contributes to plants’ ability to tolerate different types environmental stress, and to acclimate to them. The clock controls expression of a large fraction abiotic stress-responsive genes, as well as biosynthesis and signalling downstream of stress response hormones. Conversely, abiotic stress results in altered expression and differential splicing of the clock genes, leading to altered oscillations of downstream stress-response pathways. We propose a range of mechanisms by which this intimate coupling between the circadian clock and environmental stress-response pathways may contribute to plant growth and survival under abiotic stress.